Димитрова-Тодорова Л. Местните имена в Поповско - Бучко, Д. (Мовознавство, 2009)
Рецензія на книгу: Димитрова-Тодорова Л. Местните имена в Поповско. София : Акад. изд-во «Проф. Марин Дринев», 2006.— 694 с.